Deficits in the Socio-educational School Inclusion Strategy for Students with Social Difficulty in Spain during the Covid-19 Pandemic - Deibe Fernández-Simo; Xosé Manuel Cid-Fernández; María Victoria Carrera-Fernández (Center for Educational Policy Studies Journal)
Students with administrative care measures have historically faced difficulties in achieving school goals. The Covid-19 pandemic forced the declaration of a lockdown, which accelerated changes in the schools’ pedagogical actions. This investigation analyses the strategies used by the educational system to promote the academic inclusion of students who have an open protection file in the child welfare system within the context of Covid-19. Two different phases are compared: Phase 1) from the March lockdown to the end of the 2019/20 school year; Phase 2) The first six weeks of the beginning of the 2020/21 school year. Longitudinal follow-ups were carried out with adolescents in care with a sample of N = 10 (Phase 1) and N = 11 (Phase 2). Based on the grounded theory, information is supplemented by case studies through interviews with educational professionals, N = 14 (Phase 1) and N = 11 (Phase 2). The results indicate deficits of schools’ adaptability to the situation of the students suffering social exclusion and difficulties in monitoring when students do not attend school in person and do school activities at home. It is concluded that the design of the educational policy applied in the context of the pandemic does not take the social factor into account.